2015
DOI: 10.1109/tdei.2014.004566
|View full text |Cite
|
Sign up to set email alerts
|

Flashover mechanisms of bridged vacuum gaps based on cathode electric field measurement

Abstract: In bridged vacuum gaps, it is believed that the secondary electron emission avalanche (SEEA) and the resultant insulator charging play a crucial role in the progress of discharge leading to the surface flashover. This paper deals with the electric field just before the flashover that includes the accumulated SEEA charge component (E sF ) and applied geometrical field component (E gF ) on a cathode and their relation to the flashover voltage. The test gap consists of parallel disc electrodes bridged by an insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…As shown in the Figure, the value of k can be expressed as a function of R a , and it increases with the roughness. This means that the SEEA charge density decreases with the increase in R a [2]. By using the same method, we have obtained the values of k for Pyrex® and PMMA.…”
Section: Results Of K Valuesmentioning
confidence: 92%
See 2 more Smart Citations
“…As shown in the Figure, the value of k can be expressed as a function of R a , and it increases with the roughness. This means that the SEEA charge density decreases with the increase in R a [2]. By using the same method, we have obtained the values of k for Pyrex® and PMMA.…”
Section: Results Of K Valuesmentioning
confidence: 92%
“…Since the bumps on the insulator surface act as barriers for electrons in the avalanche to prevent an SEEA [2], the surface was polished or roughened in order to control the SEEA charge accumulation. The average roughness R a was 0.2, 1, 3 or 6 m. For estimating k value, we used the insulator with H=50 mm in length for each roughness.…”
Section: Measurement Of Cathode Electric Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…[48] and Naruse et al. [49] investigated the influence of surface roughness on flashover voltage for different materials such as Al 2 O 3 , SiO 2 and PTFE, indicating that rougher surfaces present higher flashover voltages. A CO 2 laser generator was adopted to create scratched lines on the surface of alumina ceramics in [50], and it was found that a much higher flashover field strength was gained with a larger scratching density.…”
Section: Interface Tailoring Methodsmentioning
confidence: 99%
“…This is possible because rougher surfaces are less sensitive to the impacts of electrons at shallow angles and thus suppress the secondary electron emission avalanche process [47]. For instance, Yamamoto et al [48] and Naruse et al [49] investigated the influence of surface roughness on flashover voltage for different materials such as Al 2 O 3 , SiO 2 and PTFE, indicating that rougher surfaces present higher flashover voltages. A CO 2 laser generator was adopted to create scratched lines on the surface of alumina ceramics in [50], and it was found that a much higher flashover field strength was gained with a larger scratching density.…”
Section: Physical Modification Methodsetching and Templatingmentioning
confidence: 99%